Could African swine fever and classical swine fever viruses enter into the United States via swine products carried in air passengers’ luggage? - Jurado, Cristina; Paternoster, Giulia; Martínez‐López, Beatriz; Burton, Kenneth; Mur, Lina (Transboundary and emerging diseases, 2019)
On average 8,000 pork derived products are annually confiscated by Customs and Border Protection at the United States (US) ports of entry such as international airports, harbours or mail offices. These swine products with unknown sanitary status could pose a risk for foreign animal diseases introduction into the US. This study aimed at analysing the risk of African swine fever virus (ASFV) and classical swine fever virus (CSFV) being introduced into the US through prohibited swine products carried by air passengers (PSPAP) and identifying locations and time periods at higher risk where and when preventive and mitigation measures should be implemented. Our results estimated that the risk for CSFV entry was seven times higher and further spread between US airports than for ASFV. Specifically, the overall mean annual probability of ASFV entry was estimated as 0.061 at 95% confidence interval (CI) [0.007, 0.216] while the probability of CSFV entry was estimated as 0.414 (95% CI [0.074, 1]). For both diseases, July and May were the months at highest risk for entry. For ASFV, the origin countries of those PSPAP that represented the highest risk (above 70% of the total risk) were Ghana, Cape Verde, Ethiopia and the Russian Federation, while for CSFV above 90% of the risk at origin was concentrated in the Dominican Republic and Cuba, followed by India, Colombia, Peru, Ecuador and China. These results could be used to implement and feed real time surveillance systems, which could potentially help customs to increase the detection rate of smuggled products, indicating when and where to look for them. Similarly, these systems could be adapted and implemented to other diseases improving the cost‐effectiveness of the resources invested in preventing entrance of diseases via air passengers’ luggage.